1991
DOI: 10.3168/jds.s0022-0302(91)78451-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isoacids, Urea, and Sulfur on Ruminal Fermentation in Sheep Fed High Fiber Diets

Abstract: The effects of isoacids, urea N, and S on ruminal fermentation of sugarcane bagasse- or corn stover-based diets were studied in sheep. Acetate production was taken as a measure of the fermentation rate. For the sugarcane bagasse diet, neither urea nor S supplementation changed ruminal acetate production. When N and S were combined, acetate production was 44% higher (3.16 vs. 2.18 mol/d). Similar effects were noted for the corn stover diet. Increasing the level of isoacids from .1 to .2 g/kg BW per d in the die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…Data for this aspect of the isoacid effect which is in agreement with Bryant [11], Dehority and Scott [18]; Gorosito et al [26], Brondani et al [10] are shown in Tables II, III and IV. CFRF and EABC fractions for oil treatment showed more cellulolytic activity than the control (P < 0.05). Recent work [22] has shown that glycerol and galactose arising from lipid hydrolysis are fermentable.…”
Section: Estimation Of Microbial Growthsupporting
confidence: 79%
See 2 more Smart Citations
“…Data for this aspect of the isoacid effect which is in agreement with Bryant [11], Dehority and Scott [18]; Gorosito et al [26], Brondani et al [10] are shown in Tables II, III and IV. CFRF and EABC fractions for oil treatment showed more cellulolytic activity than the control (P < 0.05). Recent work [22] has shown that glycerol and galactose arising from lipid hydrolysis are fermentable.…”
Section: Estimation Of Microbial Growthsupporting
confidence: 79%
“…Use of phenylacetic acid as a branched-chain fatty acid has been reported by Hefner et al [28]. The use of isoacid [10,20,43,60] is coupled with microbial growth, which also needs NH 3 as a component for protein synthesis. Lipids can also be used to manipulate the digestion and absorption of different nutrients [32,34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that Sulphur supplementation has improved gain by 12% in steer grazing sorghum-Sudan grass containing 0.08-0.12% methionine (Anonymous, 1998). The similarity in %CP for all fermented methionine supplemented samples are in agreement with the findings of Brondani et al (1991), that the effect of methionine supplementation on bacteria protein synthesis from high fibre nitrogen (N) based diets will depend on its adjustment based on the N: S ratio. If the level of nitrogen in the diet remain low, the effect of increasing levels of S on bacteria protein synthesis will remain insignificant.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, bagasse contributes little in the way of protein, lipids, and minerals to animal feed, and there are relatively few studies describing the incorporation of bagasse as roughage into animal feed without some form of processing to enhance digestibility , Romanponce et al 1975, Hegde et al 1982, Briceno et al 1987, Brondani et al 1991, Singh et al 2004. Despite this, while only a small proportion (<7.5%) of cattle in Brazil spend any significant period of time in feedlots, the size of the industry means that the sugarcane bagasse used as the primary source of roughage in finishing diets in a significant proportion (approximately 20%) of Brazilian feedlots represents a substantial amount (Oliveira and Millen 2014).…”
Section: Bagassementioning
confidence: 99%